MENGUKUR TINGKAT KESEHATAN BANK DI INDONESIA - Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Bank plays an important role in economy. Allocation of fund an circulation of money become more efficient with the existence of bank. It one factor that promotes stable economic growth.Only healthy bank can maximize its role in economic activities. The Question is what criteria of healthy bank in Indonesia. There are 5 criteria in measuring the health of bank. The criteria are Capital, Asset quality, management, earning, and liquidity (CAMEL). This paper describes and explains how these 5 criteria work.